(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Ectopsocus maindroni Badonnel, closely related to E. meridionalis Ribaga the only italian species of the genus, is reported for the first time in our country. The insect has been found on leather bags imported from India. The species is ubiquitous, almost certainly detritus feeder and probably mycophagous.